Glazy Erythema on Glans Penis in a 3-year-old Child: An Unusual Diagnosis of Zoon’s Balanitis Aided by Dermoscopy - Bhumesh K. Katakam; Kalimi V. Udhayini; Sudharani Chintagunta; Hitha A. James (Indian Dermatology Online Journal)
Zoon’s balanitis is a benign inflammatory non-venereal genital dermatosis occurring in males. Cayenne pepper spots, a characteristic feature of Zoon’s balanitis, present as erythematous macule with red, pinpoint-like dots. Uncircumcised males between the ages of 40 and 80 are usually affected. Though usually asymptomatic, some individuals may experience discomfort, burning sensations, or pruritus. The majority of the reported cases are older uncircumcised men and the lesion involves glans penis and/or prepuce. We hereby report an uncommon presentation of Zoon’s balanitis in a 3-year-old preschool child.